2018
DOI: 10.1016/j.carbpol.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-reversible supramolecular hydrogels of trehalose-type diblock methylcellulose analogues

Abstract: This paper describes the design and synthesis of new trehalose-type diblock methylcellulose analogues with nonionic, cationic, and anionic cellobiosyl segments, namely 1-(tri-O-methyl-cellulosyl)-4-[β-d-glucopyranosyl-(1→4)-β-d-glucopyranosyloxymethyl]-1H-1,2,3-triazole (1), 1-(tri-O-methyl-cellulosyl)-4-[(6-amino-6-deoxy-β-d-glucopyranosyl)-(1→4)- 6-amino-6-deoxy-β-d-glucopyranosyloxymethyl]-1H-1,2,3-triazole (2), and 4-(tri-O-methyl-cellulosyloxymethyl)-1-[β-d-glucopyranuronosyl-(1→4)-β-d-glucopyranuronosyl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…The triazole proton of compound 4b appears at 7.69 (β-anomer) and 7.70 (αanomer) ppm (α/β ratio = 2/1) (Yamagami et al 2018), while the triazole protons of compounds 5b and 6b were unable to be identified due to overlapping resonances associated with the aromatic protons of their Fmoc groups, although proton resonances of the peptide side-chains were observed.…”
Section: Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…The triazole proton of compound 4b appears at 7.69 (β-anomer) and 7.70 (αanomer) ppm (α/β ratio = 2/1) (Yamagami et al 2018), while the triazole protons of compounds 5b and 6b were unable to be identified due to overlapping resonances associated with the aromatic protons of their Fmoc groups, although proton resonances of the peptide side-chains were observed.…”
Section: Characterizationmentioning
confidence: 99%
“…Scheme displays the synthetic routes to methylcelluloses end-functionalized with peptides, as well as the control compounds. Trehalose-type methylated cellobiose derivative 1a and diblock methylcellulose analogues 1b (Yamagami et al 2018) are control compounds for peptide-functionalized methylated cellobiose derivatives 2a and 3a, and peptide-end-functionalized methylcelluloses 2b and 3b, respectively. Carbon resonances of compounds 1a, 2a, and 3a have also been assigned (see experimental section).…”
Section: Peptide-end-functionalized Methylcelluloses By Huisgen 13-dmentioning
confidence: 99%
See 3 more Smart Citations